Toward Transformative Social Protection: Integrating Economic Empowerment and Addressing Graduation Challenges in Egypt’s Takaful and Karama Program - Zayed, Mennatalla ahmed (AUC Knowledge Fountain, 2026)
This study investigates how Egypt's Takaful and Karama Program (TKP) can enhance long-term poverty reduction and program sustainability through the inclusion of economicempowerment interventions. Based on the frameworks of Social Risk Management 2.0 and Transformative Social Protection, the study places Egypt's experience in the context of international discussions about conditional cash transfers, multidimensional poverty, and graduation models. The study uses a qualitative methodology, conducting semi-structured interviews with academics, civil society experts, and policymakers. The interviews' findings are supported by content analysis of policy documents and impact evaluations on TKP and Forsa. According to the research analysis, cash transfers help alleviate poverty in the short term, but they rarely allow for a long-term escape from poverty without the help of other transformative and promotive interventions. Both programs face challenges like weak design, targeting, dependency, and limited institutional coordination. The study recommends embedding Forsa into TKP registration, redefining TKP as an asset- and livelihood-building program, and promoting gradual graduation through bundled support and extended assistance. Aligning these reforms with Egypt’s Vision 2030 and the SDGs would enable a shift from protective to transformative social protection, advancing sustainable inclusion and resilience.